Reward Circuitry and Motivational Deficits in Social Anxiety Disorder: What Can Be Learned From Mouse Models? - Carlton, Corinne N.; Sullivan-Toole, Holly; Ghane, Merage; Richey, John A. (Frontiers in Neuroscience, 2020)
Social anxiety disorder (SAD) is a common and serious psychiatric condition that typically emerges during adolescence and persists into adulthood if left untreated. Prevailing interventions focus on modulating threat and arousal systems but produce only modest rates of remission. This gap in efficacy suggests that most mainstream treatment concepts do not sufficiently target core processes involved in the onset and maintenance of SAD. This idea has further driven the development of new theoretical models that target dopamine (DA)-driven reward circuitry and motivational deficits that appear to be systematically altered in SAD. Most of the available data linking systemic alterations in DA neurobiology to SAD in humans, although abundant, remains at the level of correlational evidence. Accordingly, the purpose of this brief review is to critically evaluate the relevance of experimental work in rodent models that link details of DA function to symptoms of social anxiety. We conclude that, despite certain systematic limitations inherent in animal models, these approaches provide useful insights into human biomarkers of social anxiety including that (1) adolescence may serve as a critical period for the convergence of neurobiological and environmental factors that modify future expectations about social reward through experience dependent changes in DA-ergic circuitry, (2) females may show unique susceptibility to social anxiety symptoms when encountering relational instability that influences DA-related neural processes, and (3) separate from fear and arousal systems, the functional neurobiology of central DA systems contribute uniquely to susceptibility and maintenance of anhedonic factors relevant to human models of SAD.